Analisis Pemilihan Freight forwarder di PT XYZ dengan Metode Analytical Hierarchy Process (AHP) - Alivia Najwa; Maruf Maruf; Wenny Ananda Larasati (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study examines the importance of a reliable import process in supporting manufacturing operations. PT XYZ has experienced recurring delays in the delivery of imported raw materials under the Less than Container Load (LCL) scheme and Ex Works (EXW) terms. These delays are primarily associated with freight forwarder performance, particularly during cargo consolidation and inland distribution from the port to the company’s warehouse. In practice, the selection of freight forwarders has tended to emphasize cost considerations, often at the expense of service reliability. This condition indicates the need for a more structured approach in evaluating logistics service providers. The objective of this study is to identify key criteria in freight forwarder selection, determine their relative priorities, and rank available alternatives. The Analytical Hierarchy Process (AHP) is employed using a descriptive quantitative approach, with data collected through pairwise comparison questionnaires from respondents involved in export–import activities. The results indicate that delivery and service quality are the most influential criteria, followed by cost, responsiveness, and flexibility. These findings provide practical insight for improving decision-making in freight forwarder selection and support more reliable inbound logistics performance. This research contributes to strengthening supply chain reliability by offering a structured framework for vendor evaluation in manufacturing operations.